2019
DOI: 10.1002/2211-5463.12761
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone receptor promotes osteosarcoma cell growth and metastases

Abstract: Osteosarcoma (OS) is the primary bone malignancy in children and adolescents, with a high incidence of lung metastasis and poor prognosis. Here, we report that growth hormone receptor (GHR) is overexpressed in OS samples compared with osteofibrous dysplasia. We subsequently demonstrated that GHR knockdown inhibited colony formation, promoted cell apoptosis and decreased the number of cells at G2/M phase in 143B and U2OS cells. Furthermore, knockdown of GHR inhibited tumor growth in vivo. Together, these findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…[46][47][48] IGF-1 is produced in the liver, stimulated by GH, and plays a main role in tissue growth and development. [49][50][51][52] Higher circulating levels of IGF-1 have a profound impact on cell proliferation, differentiation, promotion of cellular longevity, and inhibition of apoptosis. 53,54 Consequently, overexpression of IGF-1/IGF-1R has been implicated in tumor formation, angiogenesis, and metastasis in various human cancer types, including OS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[46][47][48] IGF-1 is produced in the liver, stimulated by GH, and plays a main role in tissue growth and development. [49][50][51][52] Higher circulating levels of IGF-1 have a profound impact on cell proliferation, differentiation, promotion of cellular longevity, and inhibition of apoptosis. 53,54 Consequently, overexpression of IGF-1/IGF-1R has been implicated in tumor formation, angiogenesis, and metastasis in various human cancer types, including OS.…”
Section: Discussionmentioning
confidence: 99%
“…55 Thus, increasing GHR expression level will lead to higher circulating levels of IGF-1 and may eventually result in tumorigenesis. [47][48][49]53,55 Dysregulation of LEPROT is associated with various bone inflammation diseases in humans through the key inflammatory cytokines such as tumor necrosis factor alpha (TNF a) and interleukin 6 (IL-6). Several studies have highlighted that bone inflammation is a frequent precursor to initiation and progression of OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MAPK pathway and the PI3K/AKT pathway are important for pituitary tumorigenesis (34) and are activated also by the GH and IGF signaling. Osteosarcoma is the most prevalent bone malignancy in children and adolescents and is a main cause of cancer-related deaths (35). Interestingly, a recent study reported the overexpression of GHR in osteosarcoma samples and that GHR gene knockdown reduced proliferation, invasion and migration while increasing apoptosis (35).…”
Section: Mirnas and Lncrnas Regulating The Gh/igf1 Axis And Igf System In Cancer: Focus On Pituitary Adenoma Osteosarcoma And Colorectal mentioning
confidence: 99%
“…Adult height has been used as a biomarker of GH and IGF‐1 action, which is an independent risk for malignancy . Recently, it was also reported that GHR modulates osteosarcoma cell proliferation and metastasis through the phosphoinositide 3‐kinase/AKT signaling pathway . Previous studies have reported that individuals taller than 175 cm have a 20% higher risk for prostate cancer, a 22% higher risk for breast cancer and a 20–60% higher risk for colorectal cancer compared with control subjects shorter than 160 cm .…”
mentioning
confidence: 99%